Automated System of Pre-hispanic Camellones to Reduce Crop Damage Due to the Extreme Weather Event of Frost - Casas Dionisio, Luis Abelardo (2024)
This research develops the design phase of an automated system which can reduce the effects of frost, as this causes many negative effects in the high Andean communities of Peru, destroying crops and thus generating large economic losses, so the main objective is to develop an automated system of camellones against the effects of extreme weather event of frost to reduce crop losses. In the proposed methodology of the study was conducted in a field crop in a rural location in the highlands, the methodology of the VDI 2221 will be presented for the electronic design based on Arduino Uno, temperature sensors and control of two solenoid valves; as well as the mechanical design of the gates containing the valves and the camellones for the field crop that is able to maintain a constant flow and volume of water. The results obtained are a schematic design of the circuit, as well as a 3D modeling of the gates and camellones; also, through calculations the estimation of the amount of incoming and outgoing flow of water controlled by the valve, the amount of heat absorbed and released by the mass of water in the system is obtained. The design of the system of the camellones related to flow control, capacity and thermal conductivity is also feasible to execute because it is adapted to the conventional irrigation systems of the rural locality of study.